The performance of the judge in the short story «El caso de Julio Zimens» by Enrique López Albújar - Flores Heredia, Gladys (2022)
More than a century ago, the Peruvian writer Enrique López Albújar published the book Cuentos andinos (1920), a collection of ten stories generally protagonized by indigenous characters, and which have the Andean world as their narrative space. Literary critics have emphasized the foundational character of this book of stories, since it represents, for the first time, the Andean character called: The Indio. This text does not intend to discuss whether the Indian represented by López Albújar is or is not true, is or is not a criminal; but, on the contrary, our attention is focused on the study of the representation of the figure of the judge in the story «The Case of Julio Zimens». We will describe and explain our thoughts on the judge, the judicial system, and its paradoxes.